What Counts as Evidence in Child Welfare Research?. (July 2022) - Tajima, Emiko A.; Day, Angelique G.; Kanuha, V. Kalei; Rodriquez-JenKins, Jessica; Pryce, Jessica A.
In this commentary, we respond to Barth and colleagues and critique their premise that Western-based research with population-level administrative data is the best and only valid evidence on which to base child welfare policy and practice changes. We offer an alternative viewpoint on what forms of evidence should be brought to bear as we consider re-envisioning the child welfare system, highlighting the importance of lived experience and the need to consider the evidence regarding all marginalized racial and ethnic groups. We argue that evidence should represent the perspectives of those with lived experience and that collaborative child welfare research can strengthen the validity of analyses and interpretations. We hold that Barth et al. ask and answer the wrong questions. We press for deeper critical reflection, a more nuanced intersectional lens, and urgent action to address structural and institutional racism in the child welfare system.